ORAL CHANGES DURING PREMENOPAUSE - Achilova Nodira Ganievna (Web of Journals Publishing, 2025)
The premenopausal period in women is accompanied by significant hormonal changes that have a systemic effect on the body, including the tissues of the oral cavity. The purpose of this review article is to summarize current data on the characteristic changes in the oral mucosa, periodontium and the state of the dental system during this period of a woman's life. The main pathophysiological mechanisms underlying these changes, as well as their clinical manifestations and possible approaches to prevention and treatment are presented. It was originally believed that premenopausal period develops as a result of the indirect effect of estrogen deficiency on the synthesis of calcitonin and parathyroid hormone (PTH), 1,25OH2 vitamin D, and intestinal calcium absorption. That is, against the background of hypoestrogenemia, the balance between the level of calcium in the blood serum, parathyroid hormone, calcitriol, and calcitonin is disrupted, a negative calcium balance is formed, vitamin D deficiency, and secondary hyperparathyroidism develops. Calcium and vitamin D deficiency in postmenopause is observed in at least 70% of women
Keywords: Premenopausal period, hormonal imbalance, oral cavity, periodontium, xerostomia, women's health.